2010
DOI: 10.1021/ja1037287
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Covalent Bonding Interactions in a One-Dimensional Chain of a Phenalenyl-Based Singlet Biradical Molecule Having Kekulé Structures

Abstract: A novel naphthoquinoid singlet biradical (2a) stabilized by phenalenyl rings is prepared by a multistep procedure and is investigated in terms of covalent bonding interactions. The molecule 2a gives single crystals, in which a 1D chain is formed with a very short π-π contact at the overlapping phenalenyl rings. The unpaired electrons in 2a are involved in covalent bonding interactions not only within the molecule but also between the molecules in the 1D chain, and a linear conjugation is made of the alternatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 171 publications
(89 citation statements)
references
References 52 publications
5
82
2
Order By: Relevance
“…The solid 3c also showed a redshift of the lowest‐energy band in the optical spectrum with respect to the solution band of 3b . However, the shifted band of 3c was located at a higher‐energy region (centered at 7822/cm) relative to that of 1c (at 6804/cm).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The solid 3c also showed a redshift of the lowest‐energy band in the optical spectrum with respect to the solution band of 3b . However, the shifted band of 3c was located at a higher‐energy region (centered at 7822/cm) relative to that of 1c (at 6804/cm).…”
Section: Discussionmentioning
confidence: 87%
“…The single crystal of 3c , which is unsubstituted on the phenalenyl rings, afforded a 1D chain in a slipped stacking arrangement with the superimposed phenalenyl overlap, which was almost identical to that of 1c . The very short π–π contact (an average π–π distance of 3.170 Å) indicates the adequate covalent‐bonding interaction between molecules.…”
Section: Discussionmentioning
confidence: 89%
“…Intermolecular covalent bonding interactions were investigated with single crystals of tetraphenyl derivatives 19 and 20 . X‐ray analysis revealed that 19 and 20 afforded 1D chains in a slipped stacking arrangement with the superimposed phenalenyl moieties overlapping, which were almost identical to that of 13 (Figure ) . The very short π–π contacts (3.16 Å for 19 , 3.15 Å for 20 ) indicate the adequate covalent bonding interaction between molecules.…”
Section: Singlet Biradicals Based On Bisphenalenylmentioning
confidence: 89%
“…Tetraphenyl derivatives 12 and 13 of 10 and 11 were prepared by multistep syntheses. 35,36 X-ray analysis revealed that 12 and 13 form 1D stacks in a slipped stacking arrangement with a superimposed phenalenyl overlap, which was almost identical to that of 8 and 9 ( Figure 8). Very short ππ contacts (3.170 ¡ for 12, 3.122 ¡ for 13) were also observed.…”
Section: 32mentioning
confidence: 94%